Natural minerals mixture for enhancing concrete compressive strength - Abdoullah Namdar (Fracture and Structural Integrity)
The construction material quality is required to be improved in order to enhancing structure stability, optimizing construction cost and quality. The kaolin and bentonite have been mixed in equal quantity and treated by heat for 1 hour under 600 oC, 800 oC and 1000 oC to create new minerals under high temperature condition to introduce an acceptable concrete additive for achieving concrete compressive strength in early age. To study micro properties of additive-cement mixture, X-ray and FESEM experiments have been used. The results indicate that acceptable proportion of unheated kaolin-bentonite is improving the concrete compressive response. But if kaolin-bentonite mixture treated by heat under 800 oC and in quantity of 12 % has been used in concrete mixed design, then the concrete compressive strength of 7 days shows the best result. The result is due to the development of new minerals under high temperature condition in mineral mixture and also kaolin-bentonite additive change cement past crystal and lead to enhancement of nano structural cement bonding.